Human Rights Standards in European Courts and Legal Obstacles in Extradition under EU Law - Abhinav kumar (European Economic Letters (EEL), 2026)
This document discusses the impact of the human rights standards on the extradition in the framework of the European Union (EU) law with particular focus on the ongoing shift in the interrelation between the aspects of judicial cooperation and the protection of fundamental rights. Based on the European Convention on Human Rights (ECHR), and, in particular, Articles 3, 5, and 6 of the same, the paper examines the transformation of the legal scope of extradition by the European Court of Human Rights (ECtHR) and the Court of Justice of the European Union, respectively (CJEU) to ensure that efficiency is not at the expense of human dignity and the right to a fair trial. The article reviews the major transformations in the European Arrest Warrant (EAW) mechanism to the doctrine of non-refoulement, with some of the landmark cases e.g. the Soering v. case. Aranyosi and Caldararau and United Kingdom. It establishes unresolved legal conflicts between mutual recognition, sovereignty and human rights observance, especially in states with rule-of-law or detention issues. Moreover, it discusses the extraterritorial scope of the EU human rights requirements and recent cases in Ukraine and countries of the Eastern Partnership, where the conflict and the absence of stability become obstacles on the way of the fair judicial procedure. The paper concludes that the European extradition law is drifting towards a rights-based approach whereby judicial cooperation and the primacy of human rights are balanced.